2013
DOI: 10.1111/psj.12037
|View full text |Cite
|
Sign up to set email alerts
|

Centralized Governance and Student Outcomes: Excellence, Equity, and Academic Achievement in the U.S. States

Abstract: Are states with more centralized approaches to education governance more likely to have higher student achievement and lower achievement gaps between poor and nonpoor students? This article addresses that question by theorizing about the effects of political, administrative, and fiscal centralization on student outcomes. It tests competing hypotheses about the degree to which centralization across these three dimensions is associated with the promotion of academic excellence (higher achievement) and equity (na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 40 publications
1
9
0
1
Order By: Relevance
“…Second, the negative coefficient estimates for organization homophily suggest that actors are likely to form ties with different types of organizations (e.g., LEAs, state agencies, research organizations, nonprofits) to collaborate and exchange information about the needs of children on the autism spectrum, though the finding in the second model is associated with a lower degree of confidence ( p < 0.10). The heterogeneity of interactions between public and private organizations is consistent with recent education policy trends in which LEAs build partnerships with private actors to deliver various educational services (Galey, ; Manna, ; Manna & McGuinn, ). Similarly, the negative coefficient for professional homophily indicates that actors are likely to form strong, collaborative ties across professional specializations.…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…Second, the negative coefficient estimates for organization homophily suggest that actors are likely to form ties with different types of organizations (e.g., LEAs, state agencies, research organizations, nonprofits) to collaborate and exchange information about the needs of children on the autism spectrum, though the finding in the second model is associated with a lower degree of confidence ( p < 0.10). The heterogeneity of interactions between public and private organizations is consistent with recent education policy trends in which LEAs build partnerships with private actors to deliver various educational services (Galey, ; Manna, ; Manna & McGuinn, ). Similarly, the negative coefficient for professional homophily indicates that actors are likely to form strong, collaborative ties across professional specializations.…”
Section: Resultssupporting
confidence: 59%
“…For example, principals enhance compliance capacity by delegating implementation decisions to educators and administrators with relevant expertise (O'Laughlin & Lindle, ), while some LEAs reach out to nongovernmental organizations for expertise and educational strategies for students with disabilities (Parsons, ). The need for expertise is often compounded by the challenges LEAs experience in funding special education services (Cooper, ; Pitney, ; Steuernagel, ), which are further magnified in small, rural districts (Manna, ). Because the cost to educate a student with a disability can be thousands of dollars more than educating a student without a disability, Cooper (, p. 76) notes that “regionalizing and sharing services across [or within] school districts” is a common response by LEAs seeking to mitigate the complexity of special education costs and the wide range of disabilities they must accommodate.…”
Section: Beliefs Trust and Coordination In Low‐risk Policy Environmmentioning
confidence: 99%
“…Structural barriers, other than those posed by Whetten and Bozeman (1991), were not found. The fact that state education governance structures affected collaboration is not surprising given previous research noting student achievement and policy differences linked to state governance structures (see Hearn & Griswold, 1994;Koedel, 2014;Manna, 2006Manna, , 2013Tandberg, 2013). Although the finding is not surprising, it furthers the literature and knowledge in this area by demonstrating that theoretical constructs from organizational literature, such as Whetten and Bozeman's (1991) framework, can be relevant in the education field.…”
Section: Discussionmentioning
confidence: 61%
“…A series of research studies by Manna (2006Manna ( , 2013 found that structural elements of state K-12 governance -such as whether or not the state K-12 chief and state board of education was elected or appointed -had statistically significant effects on student achievement. On the higher education side, studies often examine how the type of state higher education oversight (planning, coordinating, or governing) affects policies and performance.…”
Section: State Education Governance Structuresmentioning
confidence: 99%
“…Based on the comparative analysis of IEA and IALS results for a small group of selected countries, Green (1997b) also concludes that centralized educational systems rate higher in educational achievement than decentralized ones. Both elementary and secondary education exhibited a significant move towards greater centralization in the US under the first and second George W. Bush administration according to Manna (2013). However, in several countries, regarded formerly as examples supporting the advantages of centralized systems, there has been a marked shift towards decentralization recently (see Bajomi, 2013 on France; Leung, 2004 on some East Asian countries, or Lundahl, 2002 on Sweden).…”
Section: Introductionmentioning
confidence: 99%